La formazione dei ministri di culto di recente insediamento in Italia (Stato, Chiese e pluralismo confessionale, 2017)
SOMMARIO: 1. Nuovi compiti del Diritto ecclesiastico - 2. L’attività dei ministri di culto stranieri in Italia - 3. Un nuovo orientamento nelle politiche governative - 4. Un Corso di formazione e di educazione al rispetto dei valori costituzionali – 5. Caratteristiche e limiti dell’attività di formazione.Abstract: The article addresses the issue of the formation of religious ministers and members of religious communities as stakeholders and at the same time opinion leaders of migrant communities, placing this activity among the new tasks of Ecclesiastical Law. Considering the rules governing the activity of the foreign religious ministers in Italy, the government policies adopted to promote the inclusion of migrants are re-established, highlighting the new strategies adopted by the Italian Ministry of Interior to educate to an active citizenship the population of the new settlements on national territory. The article explains in detail the didactic methodologies adopted, motivates the use of interdisciplinary and a dialogic didactic to deal with the value themes subject to a training course aimed at education and respect for constitutional values. The article ends with a critical reflection on the characteristics and limits of this training activity.